ANALISIS PEMANFAATAN DANA CORPORATE SOCIAL RESPONSIBILITY (CSR) BAGI PENINGKATAN KESEJAHTERAAN MASYARAKAT DI SEKITAR TAMBANG DI KABUPATEN KONAWE SELATAN - Tossepu, Ramadhan; Safar, Misran; Syaban, Abdul; Nerlin, Nerlin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
South Konawe Regency, which has many companies spread across several sub-districts, in implementing CSR in general, which is related to welfare, has not been felt by the community, especially those around the companies in South Konawe Regency. The aim of this research is to determine the process of allocating funds and the contribution of using Corporate Social Responsibility (CSR) funds to improve the welfare of communities around mines in South Konawe Regency. This type of research is qualitative research which is descriptive exploratory in nature which attempts to describe or describe the various realities found in this research. The sample selection method for this research was purposive. The mines sampled are divided into two categories, namely mines that have production operation status and mines that still have exploration status located in 7 (seven) sub-districts, namely Punggaluku, Laeya, Palangga, South Palangga, Lainea, Lalembu and Laonti. Data collection techniques are the observation method, questionnaire method, and documentary method. The data analysis techniques in this research are divided into three, namely data reduction, data display, and drawing conclusions or verification. The research results show that the company's CSR allocation process is carried out by the CSR sector making an annual budget plan. The budget is made based on the year's work plan and on requests from the surrounding community. However, whether the action plan from the CSR budget plan is carried out according to plan or not depends on the profit obtained by the company. So that the company in terms of distribution of Corporate Social Responsibility (CSR) funds is not carried out evenly in the community. Contributions in the use of Corporate Social Responsibility (CSR) funds are not only intended for the community but also for the company itself. The use of CSR funds for community welfare has not been felt by society in general, especially people who live in areas around the mine. Several companies in South Konawe Regency in the process of allocating CSR funds generally focus more on physical aspects such as building mosque ceilings, making curtains, making football field stands and repairing school buildings and so on.